Hydrodynamics of three phase flow in upstream pipes. Issue 1 (1st January 2018) - Edwards, Laura; Dhanpat, Darryan; Chakrabarti, Dhurjati Prasad
Abstract: In this article, work done by several researchers with respect to predictive models, three phase flow regimes and methods of identifying flow regimes were reviewed. Additionally, effects of water cut and fluid velocities on pressure drop, liquid holdup and flow regimes were also discussed. The three phases under investigation by the researchers were gas, oil and water flowing through horizontal, vertical or inclined pipes. The models reviewed were developed to anticipate liquid phase heights and pressure drop. The multi-fluid and drift-flux methods that can be applied to model the flow, were reviewed. The two main categories for the flow regimes identified were the oil-based and water-based flow patterns, where the water-based flow patterns would occur upon phase inversion. Conductance, algorithm and network mapping methods of identifying flow patterns were also reviewed. Additionally, it was seen that pressure gradients increased with superificial gas and liquid velocities and water cut had varying impacts on flow pattern transitions. Work done on the effects of temperature and pipe diameter were briefly explored. Furthermore, measurement of fluid flows, ways to measure flows and methods to detect the type of flow and simulate them were briefly investigated.